1999
DOI: 10.1159/000018061
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Nitric Oxide Production in Patients with Behçet’s Disease

Abstract: Background: Behçet’s disease is a chronic multisystemic disorder which is characterized by a relapsing systemic inflammatory process. One of the features of Behçet’s disease is endothelial dysfunction resulting from many factors. Objective and Methods: We conducted this study to show if there is any change of plasma nitrite and nitrate levels by using the enzymatic-spectrophotometric method as an indicator for nitric oxide (NO) production, considering the disease activity in patients with Behçet’s disease. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 13 publications
4
51
1
1
Order By: Relevance
“…Serum NO levels were found to be either significantly elevated 33 or decreased 34 in BD patients compared with control subjects. The major metabolic pathway for endogenously formed NO in healthy human subjects is uptake into the red blood cells and conversion to NO 3 − and methemoglobin 35 .…”
Section: Discussionmentioning
confidence: 93%
“…Serum NO levels were found to be either significantly elevated 33 or decreased 34 in BD patients compared with control subjects. The major metabolic pathway for endogenously formed NO in healthy human subjects is uptake into the red blood cells and conversion to NO 3 − and methemoglobin 35 .…”
Section: Discussionmentioning
confidence: 93%
“…Acute inflammatory indicators including α 1 -antitrypsin, α 2 -macroglobulin and ESR were reported to be increased in the active stage of BD [14]. In the present study, mean plasma concentrations for all biochemical acute-phase parameters including α 1 -antitrypsin and α 2 -macroglobulin, neutrophil count and the ESR were found to be significantly higher (for each, p < 0.01) among the patients with active BD when compared with inactive disease and the control subjects (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we reported that the levels of plasma NO metabolites in patients with active Behçet's disease were lower than normal [8]. This finding may not necessarily imply functional impairment of vascular endothelium because the source of NO metabolites in the circulation may vary.…”
Section: Discussionmentioning
confidence: 84%
“…In a previous study, we showed decreased levels of plasma NO end products, nitrite and nitrate in patients with Behçet's disease [8]. As mentioned above, the source of measured plasma NO products does not represent endothelial-derived NO synthesis.…”
Section: Introductionmentioning
confidence: 83%